PENGEMBANGAN MEDIA POP-UP BOOK UNTUK MENINGKATAKAN BERFIKIR ILMIAH PESERTA DIDIK SEKOLAH DASAR - Soraya, Anigah Rezki; Anas, Nirwana (ELSE (Elementary School Education Journal) : Jurnal Pendidikan dan Pembelajaran Sekolah Dasar, 2024)
This study aims to determine the increase in student understanding in class IV after being given a valid, practical and effective Pop-Up Book media on the material of the force motion of objects. The method used in this research is Research and Developmet (R&D), using the ADDIE development model (Analysis, Design, Development, Implementation and Evaluation). This Pop-Up Book media has been validated by several experts including media experts and material experts. The percentage of results from experts on Pop-Up Book Media gets very valid and very practical criteria with a score of 86% on media experts and a score of 84% on material experts, a score of 92% from teacher responses, a score of 98% from student responses. From the results of N-Gaind with a score of 0.87 high category, therefore this study shows that there is an effect of using this learning media on increasing students' scientific thinking in learning the force motion of objects, this can be proven in the pro-test results which have a significant increase of 93.75 which is very effective compared to the pre-test results with a percentage value of 51.25 in the ineffective category. Based on the explanation above, it can be concluded that using Pop-Up Book Media is very feasible, practical, and effective to be used in learning science on the material of the force motion of objects to improve the scientific thinking of elementary school students